Industrial training report: Pejabat Daerah dan Tanah Rembau / Nurdiana Nadhirah Noorizam - Noorizam, Nurdiana Nadhirah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This report presents my internship experience as Information Management course at Pejabat Daerah dan Tanah Rembau from 22 July 2024 until 13 September 2024. I was responsible for taking part in a variety of tasks related to data organization, document management, and preservation procedures during the internship. Through practical experience, I was able to manage documents maintained by the local government, understand the significance of preserving public documents, and ensure reliable data accessibility. This experience not only improved my technical skills, but it additionally enhanced my understanding of the responsibility of local government in ensuring accountability and integrity. The report emphasizes the value of effective management of information in public administration by reflecting on the difficulties experienced and the knowledge made throughout this great internship.